2020
DOI: 10.4018/978-1-5225-7820-8.ch001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Financial Information on Voting Behaviour

Abstract: In the public sector, citizens have been recognized as potential users of financial reporting elaborated by governments. A specific use of financial reporting by citizens is voting decisions, where they can approve or disapprove of the politicians' management. Political budget cycles literature contains many studies that evidence that politicians manage the budget in order to increase their possibilities of being reelected, but there is no consensus about the outcome. This chapter aims to study to what extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This finding contradicts Veiga & Veiga (2007), who state that increased capital expenditures positively affect the likelihood of re-election, in the pre-election period. However, Brusca et al (2019) prove that governments with higher capital investment do not have an advantage in elections. In other words, infrastructure development policies are not always popular with voters.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…This finding contradicts Veiga & Veiga (2007), who state that increased capital expenditures positively affect the likelihood of re-election, in the pre-election period. However, Brusca et al (2019) prove that governments with higher capital investment do not have an advantage in elections. In other words, infrastructure development policies are not always popular with voters.…”
Section: Discussionmentioning
confidence: 91%
“…They find the accounting ratios representing the service level and the municipal debt-related could differentiate the election result. The subsequent empirical findings (Bradbury & Scott, 2015;Brusca et al, 2019;A. Cunha et al, 2016;D.…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…Cohen et al (2019) state that the main reason for earnings management is the electoral cycle, as earnings management appears to be greater when the mayor is re-elected compared to during their first election, and that the pre-election period is conducive to earnings management. The impact that financial information has on the electorate was studied by Brusca et al (2020). These authors concluded that local governments that made higher capital investments or that presented reduced deficits do not have any electoral advantage; however, voters reward local governments with more social spending and punish local governments with higher taxes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%